Methane dry reforming over Ni/fibrous SBA-15 catalysts: Effects of support morphology (rod-liked F-SBA-15 and dendritic DFSBA-15) - Chi, Cheng Chong; Yoke, Wang Cheng; Syahida Nasuha, Bukhari; Setiabudi, H. D.; Aishah, Abdul Jalil (Elsevier, 2021)
Santa Barbara Amorphous-15 (SBA-15) is a promising molecular sieve material with its highly uniform porosity; nonetheless, its tubular pore channels discouraged mass transfer of reactants during catalysis. Herein, SBA-15 was altered by microemulsion technique to prepare two fibrous SBA-15 with distinct morphologies, viz. rod-liked F-SBA-15 and dendritic DFSBA-15. After Ni impregnation, the Ni/fibrous SBA-15 catalysts (Ni/F-SBA-15 and Ni/DFSBA-15) were catalytically evaluated with methane dry reforming (MDR). From characterization, rod-shaped F-SBA-15 had outer fibrous layer whereas dendritic DFSBA-15 consisted of a solid core with radially projected fibres. Besides, Ni/F-SBA-15 possessed uneven sized NiO but Ni/DFSBA-15 had uniform NiO dispersion. Characterization also proved that fibrillation and Ni impregnation did not alter the pristine properties of SBA-15. However, the surface attributes of SBA-15 remarkably reduced after fibrillation and Ni impregnation. The strength of metal-support (Ni-SiO2) interaction could be ranked as: Ni/DFSBA-15 > Ni/F-SBA-15 > Ni/SBA-15 (previously reported). Both Ni/fibrous SBA-15 catalysts exhibited high proportion of moderate basicity, which favoured the carbon removal via reverse Boudouard reaction. In accordance with endothermicity, the optimal temperature of MDR over both catalysts was 800 °C as greater temperature provoked conspicuous CH4 thermal decomposition. For 50 h MDR at 800 °C, both catalysts presented superior catalytic activity and stability. With a fully accessible siliceous framework, Ni/DFSBA-15 attained greater reactant conversions (84.05–87.40% and 81.80–85.60% ) than Ni/F-SBA-15 (80.30–85.80% and 76.73–84.10% ). In overall, Ni/DFSBA-15 was more coke-resistant than Ni/F-SBA-15 by virtue of its fully accessible structure, uniformly dispersed Ni phase, and stronger metal-support interaction